Pengaruh Konsentrasi dan Waktu Aktivasi Katalis Palladium pada Electroless Plating Nickel Permukaan Plastik ABS - Rahman, Muhammad Budi Nur; Sunardi, Sunardi; Wibisono, Auliandi Luthfi; Anggara, Bayu (JMPM : Jurnal Material dan Proses Manufaktur, 2018)
ABS plastic is widely used for automotive components and interior design because of its lightweight, easily shaped, strong, but low hardness, no friction-resistant, and heat resistant. Electro less plating is a method of metallization before electro plating to improve the quality and appearance. To get a good bond between plastic and metal is necessary to the activation of the palladium which is influence by concentration, temperature and activation time. The research aims to determine the influence of the palladium solution concentration and activation time of the electroless nickel plating process on surface roughness, layer thickness, hardness and wear resistance of ABS plastic. The concentration of palladium was prepared at 3%, 5% and 7% in HCl solution (37%). The activation time was carried out during 4 to 12 minutes. The research shows that those parameters increase wear resistance of the surface. In addition the activation time parameter is also found to increase layer thickness and roughness value of the specimens. Yet, those parameters are not found to affect significantly on its hardness value.